2022
DOI: 10.3389/fendo.2022.1060488
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome alterations in women with gestational diabetes mellitus and their offspring: A systematic review

Abstract: AimsGestational diabetes mellitus (GDM) is a metabolic disorder that might predispose pregnant women to develop type 2 Diabetes Mellitus or lead to severe adverse outcomes in their offspring. One of the factors that have been thought to be involved in the pathology behind this disorder is the microbiome. In this systematic review, we comprehensively review the documents regarding the microbiota alterations in different tracts of pregnant women with GDM and their offspring.MethodsA comprehensive search was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Similarly, research has shown that postpartum gut dysbiosis still exists and may affect the development of newborns (Farhat et al 2022 ). In the evolution process of GDM, probiotic supplements are appropriate for blood sugar control and provide the most powerful evidence for fetal development and postpartum (Mu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has shown that postpartum gut dysbiosis still exists and may affect the development of newborns (Farhat et al 2022 ). In the evolution process of GDM, probiotic supplements are appropriate for blood sugar control and provide the most powerful evidence for fetal development and postpartum (Mu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium is known as a beneficial acetate- and lactate-producing bacteria. The diminished relative abundance of this genus in the GDM group can be interpreted considering the role of Bifidobacteria in the fermentative metabolism, carbohydrate degradation, and intracellular uptake of short oligosaccharides [ 22 , 52 , 53 ]. These findings are consistent with the recommendation of probiotic supplementation based on this genus [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review with meta-analysis aims to update the previous reviews on this topic [ 21 , 22 ], including the new data available, summarizing and quantifying all relevant information to describe the current state of knowledge regarding the relationship between the microbiome and GDM. This review provides a comprehensive summary of the evidence on this topic, identifies areas of agreement and disagreement in the literature, and suggests directions for future research.…”
Section: Introductionmentioning
confidence: 99%
“…nucleatum, detected in the neonatal microbiome, was found to be absent in the mother's urogenital tract but present in their oral cavity. This suggests that the bacteria may have been transferred through the bloodstream due to its ability to adhere to vascular epithelium [87]. A review article from China [16] also highlighted that injecting saliva or subgingival plaque samples into mice can lead to placental infection with oral commensal species, including F. nucleatum, suggestingthat oral bacteria have the ability to travel to the feto-placental unit.…”
Section: Gestational Diabetesmentioning
confidence: 99%